E-2: FROM ANTAGONISM TO DÉTENTE: ASSESSING THE GEOPOLITICAL AND GEOSTRATEGIC CONSIDERATIONS OF PAK-RUSSIA TIES (1970-1977) - Katohar, Habib Ali; Tunio, Amar Manzoor; Gul, Sajjad (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
This research study seeks to address the pivotal period of the relationship between Pakistan and the former Soviet Union (present-day Russia) during the reign of Prime Minister Zulfiqar Ali Bhutto from 1970 to 1977 which resulted in a geopolitical shift. The study is purely based on the qualitative analysis of secondary sources. The paper reviewed and analyzed academic literature under the domain of thematic analysis. The core emphasis of the study is to investigate the bilateral political, military, socioeconomic, and cultural ties between Russia and Pakistan during the phase of Prime Minister Zulfiqar Ali Bhutto. The findings of the study suggest that for the first time in the political and diplomatic history of Pakistan and Russia, the tenure of Zulfiqar Ali Bhutto maintained ties with Russia which lasted only for a few years. However, the ties helped Pakistan militarily, economically, socially, and politically to expand its presence in regional politics. Therefore, the core emphasis of this study is to examine Pakistan’s Cold War political shift and the impact of regional dynamics which culminated in the formation of Pak-Russia ties during the 1970s phase.